Cultural diversity and biodiversity as foundation of sustainable development - Y. Purwanto; Endang Sukara; Purity Sabila Ajiningrum; Dolly Priatna (Indonesian Journal of Applied Environmental Studies, 2020)
INTRODUCTION We know that there is only one earth, there are many different worlds. Different worldviews  do not only have significant political and socio-economic repercussions but  they  also  determine  the  way  in which people perceive and interact with nature, thus forming their specific culture. Natural ecosystems cannot be understood, conserved and managed without  recognizing  the human  culture  that  shape them, since biological and cultural diversities are mutually  reinforcing  and interdependent. Together, cultural diversity and biological diversity hold the key to ensuring resilience in both social and ecological systems (Erdelen, 2003). Through the environmental sciences and  cultural  activities,  in promoting awareness and understanding of the relationships between biological and cultural diversity as a key basis for sustainable development.Beside has  high  biological  diversity  Indonesia also possesses high cultural diversity. It doesn’t marvel that Indonesia is the world’s largest archipelago, containing more than seventeen thousand island extending in an east-west direction for five thousand two hundred kilometers across the Sunda and Sahul continent shelves. The archipelago exhibits rich biodiversity that is unequalled in Asia (McNelly et al.,1990). Indonesia’s territory cover 7.7 million square kilometer, of which approximately 5.8 million square kilometers (75.3 %) is comprised of marine and coastal waters. Indonesia is located between two of Earth’s biogeographic regions: Indo-Malaya and Oceania.   The  Indo-Malaya   region   to  the   west includes Sumatra,  Kalimantan,  Java,  and Bali, and the Oceanic region to the east includes Sulawesi, Moluccas,  the  eastern  Sunda  Islands,  and  West Papua.  The vegetation types to the east and the west of the Wallace line are  divided  by  a  biogeographical boundary that extends from north to south along the Sunda Shelf. The natural  vegetation  on the shelf it self  is comprised principally  of  the Malesian  type, dominated by the commercially important Dipterocarpaceae. Vegetation to the east has greater affinities with Oceanic Austro-Pacific zone and is dominated by mixed tropical hardwood species. Deciduous monsoon forest occurs in seasonally dry areas, particularly in the southern and eastern islands such as the Lesser Sunda and the southern part of Papua. The outer islands of Sumatra,  Kalimantan, Sulawesi, Moluccas, and Papua comprise approximately 10 % of the world’s tropical rainforest. Indonesia has more tropical  forest than  any  other single Africa or Asia country, and is second only to Brazil in terms of tropical forest area. This country characterized  by an enormously varied topography of shallow coastal water, swamp, lakes, alluvial plains, volcanoes, and High Mountain ranges. This country also presents at least forty-seven distinct natural and man-made ecosystems. These ecosystem types ranges from   the   ice   mountain   ecosystem   and   alpine grassland  on the high mountains in Papua (Puncak Jaya Wijaya, at an altitude of over five thousand metres0 to variations of tropical rainforest ecosystems–  from  lowland  to  mountain  landscape,  shallow swamp to deep lakes, from mangroves to algae communities and coral reefs – as well as an ocean ecosystem reaching as deep as eight thousand meters below sea level (MoF/FAO, 1991).Unfortunately, little respect has been given to the high diversity of the archipelago, resulting in disappearance of many of these cultures. Studies to  document and learn traditional  wisdom are needed urgently,  not least because traditional  knowledge is often compatible with sustainable development objectives,  as  discussed in  the  World Summit  on Sustainable  Development, in Rio  de Janeiro,  1992 and in Johannesburg in 2002.   Meanwhile the deforestation in Indonesia occurs at an alarming rate. Forest cover decreased from about 193.7 million hectares in 1950s (Hannibal, 1950) to 119.7 million hectares in 1985 and to 100 million hectares in 1997 (GOI/World   Bank,  2000)  and   only   98   million hectares remain (FWI/GWF, 2001).The local knowledge of environment management and indigenous custom, as part of indigenous culture, is the product of long interaction between man and their environment and also results of   their   ability   for   application   the   technique adaptation to their environment. High biological diversity   has  utilized  for  economic  reason,  even though this national asset has not yet been fully developed.Dynamic interaction between people and biodiversity in Indonesia let to the creation of many different cultures  and  thus languages  and  dialects. More than  four hundred Indonesian ethnic groups are dispersed in different regions. Indonesia boasts665 different languages and dialects, with Papua accounting for 250 of these, Moluccas 133, Sulawesi105, Kalimantan  77, Nusa Tenggara  (Lesser SundaIslands) 53, Sumatra  38, Java  and Bali 9 (Grimes,1988). Such ethnics have  specific knowledge about how to manage  their environment and biodiversity surrounding them. Every ethnic has a specific culture, knowledge  and  local  wisdom  and  technique adaptation to their various environments.Concerning the cultural richness in Indonesian, besides have  advantages  also constitute  weaknesses for biodiversity resource management. One of these advantages    is   that   we   have   various   referable traditional pattern and alternative selection of space management and we have material to design system admissible management by all societies and also government. Meanwhile its weakness is that each ethnic  has  specific  pattern  according   to environmental condition and cultural level. But along with time developing marks sense decentralization of policy in Indonesian, therefore local or region policy that  based on actual  condition area  and society is more  elegant  compared  with  uniformity management   which  hasn’t  obviously  fastened  byother    area    that    has    different    culture    and environmental condition.